Public Perception on the Performance of Bus Services during Different Phases of Movement Control Order (MCO) - Kalaivani M.Vijayan,; Basil David Daniel, (Recent Trends in Civil Engineering and Built Environment, 2022)
Covid-19 pandemic that has been started since December 2019 affects the ridership of public bus transportation due to fear of contamination. Hence, this research was conducted to measure the public perception on bus service performance before and during pandemic within bus passengers at Johor. Data collection was based on online questionnaires through google form and the findings were analyzed by descriptive statistics, Spearman’s correlation analysis and mean score as well as ranking method. Based on the mean score method, the five utmost challenges faced by bus passengers are bus arrival late than schedule, unpleasant cleanliness of bus interior, seats and windows, risky travel in bus, longer average waiting time at bus stop and insecure condition of bus stop and bus. The most crucial challenge was determined to be the bus arrival later than schedule which was determined using a ranking method.